Effects of active anti-methamphetamine vaccination on intravenous self-administration in rats. (1st August 2015) - Miller, M.L.; Aarde, S.M.; Moreno, A.Y.; Creehan, K.M.; Janda, K.D.; Taffe, M.A.
Highlights: Methamphetamine addiction has no currently approved treatment medications. Vaccination produces antibodies which can sequester drug in the blood. Active vaccination attenuated the acquisition of self-administration in rats. Prophylactic vaccination against drug use is possible to achieve. Abstract: Background: d -Methamphetamine (METH) addiction is a serious public health concern for which successful treatment remains elusive. Immunopharmacotherapy has been shown to attenuate locomotor and thermoregulatory effects of METH. The current study investigated whether active vaccination against METH could alter intravenous METH self-administration in rats. Methods: Male Sprague-Dawley rats (Experiment 1: N = 24; Experiment 2: N = 18) were vaccinated with either a control keyhole-limpet hemocyanin conjugate vaccine (KLH) or a candidate anti-METH vaccine (MH6-KLH) or. Effects of vaccination on the acquisition of METH self-administration under two dose conditions (0.05, 0.1 mg/kg/inf) and post-acquisition dose-substitution (0, 0.01, 0.05, 0.20 mg/kg/inf, Experiment 1; 0.01, 0.05, 0.10, 0.15 mg/kg/inf, Experiment 2) during steady-state responding were investigated. Plasma METH concentrations were determined 30 min after an acute challenge dose of 3.2 mg/kg METH. Results: Active vaccination inhibited the acquisition of METH self-administration under the 0.1 mg/kg/inf dose condition, with 66% of the MH6-KLH-vaccinated rats compared to 100% of the controls reaching criteria, and produced transient and dose-dependent effects on self-administration during the maintenance phase. Under the 0.05 mg/kg/inf dose condition, MH6-KLH-vaccinated rats initially self-administered more METH than controls, but then self-administration decreased across the acquisition phase relative to controls; a subsequent dose–response assessment confirmed that MH6-KLH-vaccinated rats failed to acquire METH self-administration. Finally, plasma METH concentrations were higher in MH6-KLH-vaccinated rats compared to controls after an acute METH challenge, and these were positively correlated with antibody titers. Conclusions: These data demonstrate that active immunopharmacotherapy for METH attenuates the acquisition of METH self-administration.